Konsep Perdamaian Agama Islam sebagai Ummat Khalayak dalam Surah Al-Hujurat Ayat 13 - Dwi Cahyati, Ernah; Ahmad Rizal, Derry (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2022)
This article seeks toexplain that humans know each other among religious people in the Qur'an Surah Al-Hujurat: 13 and as an interpretation shows the greatness of God that man was created to have a high sense of tolerance. In this article, an important meaning is found, namely God's call for mankind in the world to know with each other regardless of anything, as well as the basic concept of Islam that provides peace and affection between fellow creatures of God. Through this paper, a little review of the principles of Islam as a religion of peace. Surah Al-Hujurat: 13 includes surah which supports the concept of rahmatan lil alamin.